HYDRODYNAMIC AND ENVIRONMENTAL CHARACTERISTICS DURING DRY SEASON IN THE HAU RIVER MOUTH AREA - Tien, Nguyen Ngoc; Thanh, Nguyen Trung; Dang, Vu Hai (Vietnam Journal of Marine Science and Technology, 2015)
This study shows some results of hydrodynamic and environmental characteristics in the Hau river mouth area during dry season (April). Hydrodynamic and environmental characteristics are analyzed from different field data which are carried out in the framework of science and technological cooperation programme between Vietnam and USA (2013 - 2015) and VAST.DLT.06/15-16 (2015 - 2016) project. The preliminary results show that hydrodynamic characteristics, salinity and suspended particulate matter (SPM) concentration in the Hau river are strongly affected by tidal regime.